Chemotherapy‐induced immunogenic modulation of tumor cells enhances killing by cytotoxic T lymphocytes and is distinct from immunogenic cell death. Issue 3 (16th March 2013) - Hodge, James W.; Garnett, Charlie T.; Farsaci, Benedetto; Palena, Claudia; Tsang, Kwong‐Yok; Ferrone, Soldano; Gameiro, Sofia R.
Abstract : Certain chemotherapeutic regimens trigger cancer cell death while inducing dendritic cell maturation and subsequent immune responses. However, chemotherapy‐induced immunogenic cell death (ICD) has thus far been restricted to select agents. In contrast, several chemotherapeutic drugs modulate antitumor immune responses, despite not inducing classic ICD. In addition, in many cases tumor cells do not die after treatment. Here, using docetaxel, one of the most widely used cancer chemotherapeutic agents, as a model, we examined phenotypic and functional consequences of tumor cells that do not die from ICD. Docetaxel treatment of tumor cells did not induce ATP or high‐mobility group box 1 (HMGB1) secretion, or cell death. However, calreticulin (CRT) exposure was observed in all cell lines examined after chemotherapy treatment. Killing by carcinoembryonic antigen (CEA), MUC‐1, or PSA‐specific CD8 + CTLs was significantly enhanced after docetaxel treatment. This killing was associated with increases in components of antigen‐processing machinery, and mediated largely by CRT membrane translocation, as determined by functional knockdown of CRT, PERK, or CRT‐blocking peptide. A docetaxel‐resistant cell line was selected (MDR‐1 +, CD133 + ) by continuous exposure to docetaxel. These cells, while resistant to direct cytostatic effects of docetaxel, were not resistant to the chemomodulatory effects that resulted in enhancement of CTL killing. Here, we provide an operational definition of "immunogenic modulation, " where exposure of tumor cells to nonlethal/sublethal doses of chemotherapy alters tumor phenotype to render the tumor more sensitive to CTL killing. These observations are distinct and complementary to ICD and highlight a mechanism whereby chemotherapy can be used in combination with immunotherapy. Abstract : What's new? Some chemotherapies not only kill cancer cells, but also enhance immune responses against those cells. In this study, the authors found that when tumor cells were exposed to nonlethal doses of docetaxel, they became more sensitive to killing by cytotoxic T lymphocytes. This process appears to be mediated by a number of molecules, including calreticulin. Even tumor cells that were resistant to docetaxel became more susceptible to lysis by CTLs. These results suggest that chemotherapy combined with immunotherapy might improve outcomes in patients who have failed chemotherapy alone.